2011
DOI: 10.1093/jpepsy/jsr018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome Research in Rural Pediatric Populations: The Challenge of Recruitment

Abstract: Strategies to improve recruitment and recommendations for future recruitment efforts in pediatric psychology treatment outcome research for children and families from rural areas are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Rural families often travel longer distances (Lim et al, 2011;Pierce & Scherra, 2004) and spend more time commuting for work, school, medical appointments, and recreational activities. Time required to travel may make it difficult for families to juggle children participating in multiple activities.…”
Section: Transportation and Distancementioning
confidence: 99%
See 3 more Smart Citations
“…Rural families often travel longer distances (Lim et al, 2011;Pierce & Scherra, 2004) and spend more time commuting for work, school, medical appointments, and recreational activities. Time required to travel may make it difficult for families to juggle children participating in multiple activities.…”
Section: Transportation and Distancementioning
confidence: 99%
“…The implementation and generalizability of these programs in community settings, and with families from rural areas, has been limited. Downloaded by [University of Auckland Library] at 16:12 13 October 2014 Janicke and colleagues (Janicke et al, 2011;Janicke et al, 2008) examined the effectiveness of behavioral family-based weight management group programs for overweight and obese rural children and their parents delivered through CES. Results from the pilot feasibility study (Janicke et al, 2008) revealed significant changes in weight status at a six-month follow up for both the behavioral family and behavioral parent interventions compared to a wait list control.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other reasons cited by families for dropping from services are attributed to the program and program staff. Specifically, the program’s approach may not be compatible with the family’s needs, the families do not believe the program will be beneficial, or the program staff may come across as too judgmental and/or be seen as outsiders (Gross, Julion, & Fogg, 2001; Ingoldsby, 2010; Lim, Follansbee-Junger, Crawford, & Janicke, 2013). …”
Section: Introductionmentioning
confidence: 99%